Evolution of Frozen Section in Carcinoma Breast: Systematic Review - Manjit Kaur Rana; Amrit Pal Singh Rana; Uttam Sharma; Tushar Singh Barwal; Aklank Jain (International Journal of Breast Cancer)
Background. The frozen section (FS) has been a good technique in surgical management of breast lesions since many years. But complete agreement and cooperation have not been achieved everywhere among surgeons and pathologists especially in the developing countries. FS undergoes continuous criticism due to various shortcomings but continued to be evaluated especially in developing countries. Objectives. This review was conducted to synthesize information on the use of frozen section in carcinoma breast. Data Sources. The MEDLINE database for frozen section since its origin and its implication in recent breast surgery techniques was studied. Study Eligibility Criteria. Sixty-five articles were reviewed with complete analysis on FS in both benign and malignant breast lesions. Study Appraisal and Synthesis Methods. The analysis of frozen section was done as a diagnostic tool in breast lesions, margin status in breast conservative surgery in carcinoma breast, and sentinel lymph node and use of immunohistochemistry for sentinel lymph node FS. Results. It was analysed that the FS gives accurate results in margin status analysis, decreasing rerecurrence. Conclusion. The accuracy of FSA, low recurrence rate, avoidance of reoperation, and good cosmesis are the key points of its use in breast conservative surgery. Its use in sentinel lymph node biopsy (SLNB) is equivocal. However, application of immunohistochemistry on frozen section of SLNB is an evolving trend in today’s era.